APPLICATION OF ELEMENTS OF DISTANCE LEARNING IN THE TRAINING OF MASTERS - Elena Gerasimova; Irina Panova (Вестник Северо-Кавказского федерального университета, 2022)
In the article the questions of e-learning from graduate students, shows an exemplary structure of e-learning course, the content of the topics, included in its composition. As an alternative technical platform that allows you to organize training with application of distance educational technologies, are the learning management system Moodle. For the course "Interactive forms and methods of teaching biology" studied in the master, developed a set of electronic training materials in accordance with the requirements of the electronic courses at the University. The article describes the structure of some academic topics created course shows the methods and forms ofpresentation of works of students, in particular, with the use of network services Web 2.0; described models of interaction of the teacher and students as participants in e-learning course.